Dipole carbazole ammonium salt passivation material, preparation method thereof and application of dipole carbazole ammonium salt passivation material in perovskite solar cell
By using Polarizohydrazole Salt as the passivation material, the problem of insufficient thermal stability of existing passivation materials was solved, and the performance of the solar battery performance of the perovskite was achieved, and the photoelectric conversion efficiency reached a high level.
Patent Information
- Application Number
- CN202411298115.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-28
AI Technical Summary
The thermal stability of existing passivation materials is poor, affecting the performance of perovskite solar cells.
It is used as a passivation material to use the puppet chitazole amohydramazole salt, and the thermal stability is enhanced through the rigid area of the trifle -co -structure extension of the Kaazazo group to enhance the heat stability, and the surface of the perovskite is controlled by introducing the Polar unit.
It has significantly improved the performance of the solar battery of perovskite, including the improvement of the opening voltage and filling factors. The photoelectric conversion efficiency reached 24.71 % and 21.02 %.
Smart Images

Figure CN119371350A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite solar cells, and particularly relates to a preparation method and a passivation method of a universal dipole carbazole ammonium salt passivation material. Background Art
[0003] As a new generation of thin-film solar cells, perovskite solar cells have entered a period of rapid development since their discovery. In the past decade, their photoelectric conversion efficiency has increased from the initial 3.8% to the current 26.15%, which has far-reaching development prospects and application value. The organic-inorganic halide perovskite components are generally composed of Cs + , FA + 、MA + , Pb 2+ ,I - Br - Plasma composition, this type of polycrystalline ionic compound (ABX3) active layer often has a variety of classic defects such as grain boundaries and surface interface dangling bonds in the current conventional spin coating process. Such defects are often the main factor leading to reduced device efficiency. After being doped and modified with organic ion salts such as methylammonium chloride and guanidine thiocyanate, the perovskite grains become larger, thereby reducing the number of grain boundaries in the film, and to a certain extent reducing the impact of defects in the perovskite film. At this time, the A-site or X-site defects caused by the dangling bonds on the surface of the perovskite crystal and the direct interface contact between different films are closely related to the device performance, so surface passivation is often an effective means to improve the performance of perovskite devices.
[0004] Common passivators such as propylene diammonium iodide or phenylethyl ammonium iodide have their own characteristics. Among them, propylene diammonium iodide is more focused on field effect passivation. While enhancing the n-type characteristics of the perovskite surface, it can also reduce the interface damage caused by the contact between the electron transport layer and the perovskite. Depending on the concentration and annealing temperature, phenylethyl ammonium iodide often reflects the effect of chemical passivation or two-dimensional perovskite passivation. However, the above two types of passivators are mainly composed of alkyl chains or separate benzene rings, which greatly reduces the thermal stability of the passivator itself, resulting in poor thermal stability of the overall perovskite device. Therefore, it is necessary to increase the rigid conjugated part in the passivator. In addition, after the dipole is introduced into the passivation material, the distribution of the electron cloud on the passivation material can be affected according to the direction of the dipole and the size of the dipole moment, thereby affecting the change in the surface work function of the perovskite. A more suitable energy level contact will be conducive to the interlayer transmission of carriers, thereby reducing the internal reverse built-in electric field during the period, further improving the passivation effect of the material, and obtaining a high-performance device.
[0005] In summary, as a passivation material, dipole carbazole ammonium salt has a more rigid structure, which can greatly improve its own thermal stability. At the same time, its flexible construction method also facilitates the introduction of different dipole units to passivate different perovskite components. It is an organic optoelectronic material with commercial potential. Summary of the invention
[0006] The purpose of the present invention is to improve the poor thermal stability of existing passivation materials by increasing the conjugated area. A dipole unit is introduced to regulate the surface work function of the perovskite, while reducing the carrier recombination of the perovskite film, enhancing the interface contact and energy level alignment with the electron transport layer, so as to obtain a higher performance perovskite solar cell device. The best photoelectric conversion efficiency of the organic-inorganic perovskite solar cell and the inorganic perovskite solar cell prepared by the spin coating process exceeds 24.8% and 21.02%, respectively.
[0007] The technical solution adopted by the present invention is:
[0008] A dipole carbazole ammonium salt passivation material having a chemical structure of formula (8):
[0009]
[0010] The present invention further provides a method for preparing the compound of formula (8), comprising the following steps:
[0011] S1: reacting the compound of formula (1) with the compound of formula (2) to produce the compound of formula (3);
[0012]
[0013] S2: reacting the compound of formula (3) with the compound of formula (4) to generate the compound of formula (5);
[0014]
[0015] S3: subjecting the compound of formula (5) to a reduction reaction to generate a compound of formula (6);
[0016]
[0017] S4: ionizing the compound of formula (6) to generate the compound of formula (8);
[0018]
[0019] Preferably, in S1, under the protection of inert gas, the compound of formula (1) and the compound of formula (2) are added to a reaction container, stirred for 5 minutes, and then potassium hydroxide aqueous solution and tetrabutylammonium bromide are added in sequence, and heated at 70°C for 8 to 16 hours to obtain a compound of formula (3), wherein the compound of formula (2) is the solvent used in the reaction, and the amounts of the remaining compounds participating in the reaction are calculated based on the mass balance standard, and the ratio of compound of formula (1): potassium hydroxide aqueous solution: tetrabutylammonium bromide = 1:1.5 to 4:0.03 to 0.1.
[0020] Preferably, in S2, at room temperature, the compound of formula (3), the compound of formula (4) and DMF are added to a reaction container, and reacted at 80-100° C. for 10-20 hours to obtain the compound of formula (5), wherein the amount of the compound involved in the reaction is calculated based on the mass balance standard, and the ratio of compound of formula (3) to compound of formula (4) is 1:1.5-3.
[0021] Preferably, in S3, at room temperature, the compound of formula (5), ethanol and tetrahydrofuran are added to the reaction container in sequence, heated to 60°C, hydrazine hydrate is added dropwise, and refluxed for 1-2h. According to the dissolution conditions of different reactants, the ratio of the added auxiliary dissolving solvent tetrahydrofuran (THF) and ethanol is between 1:50 and 1:200. After the reaction is completed, water is used for quenching, and stirring is continued for 1-5h. After multiple extractions with a large amount of water / a small amount of dichloromethane, no further purification is required after thorough removal of water. The compound of formula (6) is obtained, wherein the amount of the compound involved in the reaction is calculated based on the mass balance standard, and the compound of formula (5): hydrazine hydrate = 1:2-6.
[0022] Preferably, in S4, under ice bath conditions, the compound of formula (6) and ethanol are added to a reaction container, and hydroiodic acid aqueous solution is added dropwise using a separatory funnel. After stirring for two hours, the solvent is evaporated, and the equivalent should be controlled in the range of 1 to 1.5 eq. The obtained solid is washed with a mixed solvent of ether: dichloromethane 100: 1 to 10: 1, and recrystallized with ethanol or methanol. The amount of the compound involved in the reaction is calculated based on the mass balance standard, and the compound of formula (6): hydroiodic acid = 1: 1 to 1.5.
[0023] The present invention further provides the use of the above-mentioned dipole carbazole ammonium salt passivation material in perovskite solar cells.
[0024] The beneficial effects of the present invention are as follows: 1. The dipole carbazole passivation material provided by the present invention is an organic small molecule ammonium salt based on the dipole carbazole functional structure, and its chemical formula is C 14 H 14N2ClI, through the ternary conjugated structure of the carbazole group, expands the rigid area of conventional passivation materials and enhances the intrinsic thermal stability of the material. At the same time, carbazole also provides more electron clouds than the benzene ring, which is conducive to the chemical passivation of this type of ammonium salt passivation material and can better fill the A-site and X-site defects on the surface of the perovskite; the introduction of the dipole makes the interface contact between the passivated perovskite and the electron transport layer better, so that the device obtains a higher open circuit voltage and fill factor, and the performance improvement effect is obvious;
[0025] 2. The application of the hole transport material provided by the present invention in perovskite solar cells. The test results show that ( Figure 4 ): The short-circuit photocurrent density (Jsc) in organic-inorganic perovskite solar cells reached 25.27 mA cm -2 , the open circuit voltage (Voc) is 1.178 V, the fill factor (FF) is 82.98%, the photoelectric conversion efficiency (PCE) reaches 24.71%, and in the inorganic perovskite device, Jsc = 20.35 mA cm -2 , Voc=1.232V, FF=83.86%, PCE=21.02%, that is, the passivation material has practical significance for improving the efficiency of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A schematic diagram of the structure of a dipole carbazole ammonium salt passivated organic-inorganic perovskite solar cell according to a specific embodiment 1 of the present invention;
[0027] In the figure, 1 is a glass / FTO substrate, 2 is a self-assembled hole layer, and 3 is an organic-inorganic perovskite film, whose specific components are Cs 0.05 MA 0.05 FA 0.9 PbI 2.85 Br 0.15 , 4 is a mixed passivation layer of propylene diammonium salt (PDAI2) and dipolar carbazole ammonium salt, 5 is a PCBM electron transport layer, 6 is a BCP barrier layer, and 7 is a metal silver electrode;
[0028] Figure 2 This is a schematic structural diagram of a dipole carbazole ammonium salt passivated inorganic perovskite solar cell according to a specific embodiment 3 of the present invention;
[0029] In the figure, 10 is a glass / FTO substrate, 20 is a hybrid self-assembled hole layer, 30 is an inorganic perovskite film, whose component is specifically CsPbI3, 40 is a mixed passivation layer of propylene diammonium salt (PDAI2) and dipolar carbazole ammonium salt, 50 is a PCBM electron transport layer, 60 is a BCP barrier layer, and 70 is a metal silver electrode;
[0030] Figure 3The JV curve of the organic-inorganic perovskite solar cell passivated by mixing PDAI2 and dipolar carbazole ammonium salt in Example 2, wherein the concentration of PDAI2 solution is 0.5 mg / ml, and the concentration of dipolar carbazole ammonium salt solution is 0.2 mg / ml;
[0031] Figure 4 The JV curve of the inorganic perovskite solar cell passivated by mixing PDAI2 and dipolar carbazole ammonium salt in Example 3, wherein the concentration of PDAI2 solution is 0.5 mg / ml, and the concentration of dipolar carbazole ammonium salt solution is 0.2 mg / ml;
[0032] Figure 5 The JV curve of the organic-inorganic perovskite solar cell passivated by PDAI2 alone in Comparative Example 1, where the concentration of PDAI2 solution is 0.5 mg / ml;
[0033] Figure 6 The JV curve of the inorganic perovskite solar cell passivated by PDAI2 alone in Comparative Example 2, where the concentration of PDAI2 solution is 0.5 mg / ml; DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Embodiment 1:
[0036] A dipole carbazole ammonium salt passivation material has the chemical structure of the following formula (8):
[0037]
[0038] S1: reacting the compound of formula (1) with the compound of formula (2) to produce the compound of formula (3);
[0039]
[0040] Specifically, in this step, under inert gas conditions, 1.5 g of the compound of formula (1) is added to a 250 mL two-necked flask and dissolved with 15 ml of the compound of formula (2). After stirring for 5 minutes, 12 ml of a 50% potassium hydroxide aqueous solution is added dropwise, followed by adding 9.59 mg of tetrabutylammonium bromide, followed by heating to 70° C. and stirring for 8 hours; water is added to quench, dichloromethane is used for extraction, and ethanol is added in small amounts and multiple times during reduced pressure distillation to remove the solvent and water; the crude product is purified by column chromatography (eluent: petroleum ether / dichloromethane=100 / 1-30 / 1) to obtain 1.18 g of the compound of formula (3) as a white fluffy powder with a yield of 51.5%.
[0041] S2: reacting the compound of formula (3) with the compound of formula (4) to generate the compound of formula (5);
[0042]
[0043] Specifically, at room temperature, 1.18 g of the compound of formula (3), 1.42 g of the compound of formula (4) and 20 ml of DMF were added to a 100 ml two-necked bottle, reacted at 85° C. for 14 hours to obtain the compound of formula (5), quenched with water, extracted with dichloromethane, extracted 5 times and then distilled under reduced pressure, and the solvent and water were removed by adding ethanol in small amounts and multiple times. The obtained product was directly used in the next reaction (calculated based on the full yield);
[0044] S3: subjecting the compound of formula (5) to a reduction reaction to generate a compound of formula (6);
[0045]
[0046] Specifically, at room temperature, the mixed product of the previous step, 80 ml of ethanol and 10 ml of tetrahydrofuran are added to a 250 ml two-necked bottle in sequence, and when heated to 60° C., 0.9 ml of 80% hydrazine hydrate solution is added dropwise, and refluxed for 2 hours. After the reaction is completed, the mixture is quenched with water, and after continuous stirring for 5 hours, it is extracted 8 times with a large amount of water / a small amount of dichloromethane. During the reduced pressure distillation, ethanol is added in small amounts and multiple times to remove the solvent and water to obtain a dark yellow viscous liquid. Here, the product still contains a small amount of solvent and water, but it is directly used in the next reaction without further treatment (calculated according to the full yield).
[0047] S4: ionizing the compound of formula (6) to generate the compound of formula (8);
[0048]
[0049] Specifically, in this step, the product of the previous step was dissolved in 20 ml of ethanol and added to a 250 ml two-necked flask under ice bath conditions, 0.5 ml of hydroiodic acid aqueous solution was added dropwise using a separatory funnel, and the solvent was evaporated after stirring for two hours. The obtained solid was washed three times with a mixed solvent of ether: dichloromethane in a ratio of 10:1, and then washed three times with a mixed solvent of ether: dichloromethane in a ratio of 50:1. 0.5 ml of ethanol was added to the obtained white solid, and the solution was heated to boiling. After standing and cooling overnight, it was filtered to obtain 331 mg of white powder product 8. After three consecutive steps of recrystallization, the yield was 23.3%.
[0050] Embodiment 2:
[0051] This embodiment provides an application of the dipole carbazole passivation material (8) prepared in embodiment 1 in an organic-inorganic perovskite solar cell. Figure 1 , the preparation method comprises:
[0052] S1: ultrasonically clean the FTO conductive glass with detergent, deionized water and isopropyl alcohol for 30 minutes each, and use it as a transparent conductive substrate 1 for standby use;
[0053] S2: The cleaned transparent conductive substrate 1 was blown dry with nitrogen, treated with UV for 20 minutes, and then transferred to a nitrogen glove box. 150 μl of MeO-2PACz solution was spin-coated on one side of the transparent conductive substrate 1, and then annealed on a hot plate at 100°C for 10 minutes;
[0054] S3: Divide the group into Cs 0.05 MA 0.05 FA 0.9 PbI 2.85 Br 0.15 The perovskite is dissolved in a mixed solvent of dimethylformamide (DMF): dimethyl sulfoxide (DMSO) with a volume ratio of 4:1 to prepare a perovskite solution with a concentration of 1.5M for use. Spread 35μl of the prepared solution on a substrate with an area of 2cm×2cm and spin coat it in two stages. The first stage is at a rotation speed of 1000rpm. After 10s, it turns to the second stage. The second stage spin coating speed is 6000rpm and ends after 30s. 5s before the end, 80μl of anti-solvent chlorobenzene (CB) is added dropwise. After the spin coating is completed, the sample is quickly placed on a 100℃ hot plate and annealed for 30 minutes. The thickness of the prepared perovskite film is about 700nm;
[0055] S4: Dissolve 0.5 mg PDAI2 and 0.2 mg compound of formula (8) in 1 ml isopropanol as a mixed passivation solution. After 45 μl of the mixed solvent is added dropwise to the surface of the perovskite prepared in S3, spin coating is immediately started at a speed of 3000 rpm for 30 seconds. After the spin coating is completed, the sample is quickly placed on a 100°C hot plate and annealed for 10 minutes.
[0056] S5: Prepare 20mg / ml PCBM chlorobenzene solution and 0.5mg / ml BCP isopropanol solution respectively and set aside. Spin coat the PCBM solution after the passivation layer at a speed of 2500rpm for 30s, and then directly spin coat the BCP solution at a speed of 6000rpm for 40s.
[0057] S6: Using thermal evaporation process, 80nm of metallic silver is evaporated on the sample obtained after step S5 as an electrode, and the evaporation rate is
[0058] The structure of the prepared organic-inorganic perovskite-based solar cell is as follows Figure 1 As shown; its performance test: at AM1.5, 100mW cm -2 Under the irradiation of standard light intensity, the open circuit voltage of the solar cell prepared in this embodiment is 1.178V, and the short circuit current density is 25.27mA cm -2 , the filling factor is 82.98%, such as Figure 3 As shown, the efficiency is 24.71%.
[0059] Embodiment 3:
[0060] This embodiment provides an application of the dipole carbazole passivation material (8) prepared in embodiment 1 in an inorganic perovskite solar cell. Figure 2 , the preparation method comprises:
[0061] S1: ultrasonically clean the FTO conductive glass with detergent, deionized water and isopropyl alcohol for 30 minutes each, and use it as a transparent conductive substrate 10 for standby use;
[0062] S2: The cleaned transparent conductive substrate 10 was blown dry with nitrogen, UV treated for 20 minutes, and then transferred to a nitrogen glove box. 40 μl of MeO-2PACz solution was spin-coated on one side of the transparent conductive substrate 1, and then annealed on a hot plate at 100°C for 10 minutes, followed by spin-coating 70 μl of P3CT solution, and then annealing on a hot plate at 100°C for 10 minutes;
[0063] S3: Dissolve the perovskite with the component of CsPbI3 in DMF solvent to prepare a perovskite solution with a concentration of 0.65M for use. Preheat the sample obtained after step S2 at 70°C for 3 minutes, spread 25μl of the prepared perovskite solution on a substrate with an area of 1.5cm×1.5cm, and spin coat at a speed of 2500rpm, and finish after 25s. After spin coating, quickly place the sample on a 210°C heating plate and anneal for 10 minutes. The above process is carried out in an air environment with 20% humidity. After annealing, quickly transfer the sample to a nitrogen glove box;
[0064] S4: Dissolve 0.5 mg PDAI2 and 0.2 mg compound of formula (8) in 1 ml isopropanol as a mixed passivation solution. After 45 μl of the mixed solvent is added dropwise to the surface of the perovskite prepared in S3, spin coating is immediately started at a speed of 3000 rpm for 30 seconds. After the spin coating is completed, the sample is quickly placed on a 100°C hot plate and annealed for 10 minutes.
[0065] S5: Prepare 20mg / ml PCBM chlorobenzene solution and 0.5mg / ml BCP isopropanol solution respectively and set aside. Spin coat the PCBM solution after the passivation layer at a speed of 2500rpm for 30s, and then directly spin coat the BCP solution at a speed of 5000rpm for 30s.
[0066] S6: Using thermal evaporation process, 80nm of metallic silver is evaporated on the sample obtained after step S5 as an electrode, and the evaporation rate is
[0067] The structure of the prepared inorganic perovskite-based solar cell is as follows Figure 2 As shown; its performance test: at AM1.5, 100mW cm -2 Under the irradiation of standard light intensity, the open circuit voltage of the solar cell prepared in this embodiment is 1.232V, and the short circuit current density is 20.35mA cm -2 , the filling factor is 83.86%, such as Figure 4 As shown, the efficiency is 21.02%.
[0068] Comparative Example 1:
[0069] This comparative example provides the application of a single PDAI2 passivation material in an organic-inorganic perovskite solar cell. The preparation method is basically the same as that in Example 2, except that:
[0070] S4: Dissolve 0.5 mg PDAI2 in 1 ml isopropanol as a mixed passivation solution. After adding 45 μl of the mixed solvent to the perovskite surface, spin coating was immediately started at a speed of 3000 rpm for 30 seconds. After the spin coating was completed, the sample was quickly placed on a 100 ° C hot plate and annealed for 10 minutes.
[0071] The structure of the prepared organic-inorganic perovskite-based solar cell is as follows Figure 1 As shown; its performance test: at AM1.5, 100mW cm -2 Under the irradiation of standard light intensity, the open circuit voltage of the solar cell prepared in this embodiment is 1.149V, and the short circuit current density is 24.86mA cm -2 , the filling factor is 82.76%, such as Figure 5As shown, the efficiency is 23.65%.
[0072] Comparative Example 2:
[0073] This comparative example provides the application of a single PDAI2 passivation material in an inorganic perovskite solar cell. The preparation method is basically the same as that in Example 3, except that:
[0074] S4: Dissolve 0.5 mg PDAI2 in 1 ml isopropanol as a mixed passivation solution. After adding 45 μl of the mixed solvent to the perovskite surface, spin coating was immediately started at a speed of 3000 rpm for 30 seconds. After the spin coating was completed, the sample was quickly placed on a 100 ° C hot plate and annealed for 10 minutes.
[0075] The structure of the prepared inorganic perovskite-based solar cell is as follows Figure 2 As shown; its performance test: at AM1.5, 100mW cm -2 Under the irradiation of standard light intensity, the open circuit voltage of the solar cell prepared in this embodiment is 1.144V, and the short circuit current density is 20.38mA cm -2 , the filling factor is 82.78%, such as Figure 6 As shown, the efficiency is 19.30%.
[0076] In summary, after passivation with the compound of formula (8), the performance of both the organic-inorganic perovskite device and the inorganic perovskite device is greatly improved, specifically in terms of the improvement in open circuit voltage and fill factor. This phenomenon further confirms that this type of dipole carbazole ammonium salt passivation material reduces the carrier recombination of the perovskite active layer and enhances the interface contact between the perovskite and the electron transport layer, and is an effective organic photoelectric passivation material.
[0077] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A dipole carbazole ammonium salt passivation material, characterized in that: This type of passivation material can inhibit carrier recombination at the perovskite interface and promote carrier transport between the perovskite and the electron transport layer. At the same time, it can adapt to different perovskite components and single-cell or stacked perovskite solar cells, and can obtain higher photoelectric conversion efficiency and lasting device stability. The dipole carbazole ammonium salt passivation material has the chemical structure of formula (8):
2. The method for preparing the dipole carbazole ammonium salt passivation material according to claim 1, characterized in that: The steps include: S1: reacting the compound of formula (1) with the compound of formula (2) to produce the compound of formula (3); S2: reacting the compound of formula (3) with the compound of formula (4) to generate the compound of formula (5); S3: subjecting the compound of formula (5) to a reduction reaction to generate a compound of formula (6); S4: ionizing the compound of formula (6) to generate the compound of formula (8); 3. The preparation method according to claim 2, characterized in that: In step S1, in the dipolar carbazole alkylation reaction, under the protection of inert gas, the compound of formula (1) and the compound of formula (2) are added to a reaction container, and after stirring, potassium hydroxide aqueous solution and tetrabutylammonium bromide are added in sequence, and heated to react to obtain a compound of formula (3), wherein the compound of formula (1): potassium hydroxide aqueous solution: tetrabutylammonium bromide = 1: 1.5-4: 0.03-0.1; by directly using dibromoethane as the reaction solvent for the compound of formula (2), a unilateral reaction is ensured to generate a single unilateral product; the potassium hydroxide is added in the form of a 50% aqueous solution, and the equivalent is in the range of 1.5-4eq, and the equivalent of tetrabutylammonium bromide as a phase transfer catalyst is in the range of 0.03-0.1eq; the selected dipole unit includes but is not limited to electron-withdrawing groups such as halogen, ester group, and cyano group.
4. The preparation method according to claim 2, characterized in that: In the first step of the Gabriel reaction using the passivation material in step S2, at room temperature, a compound of formula (3), a compound of formula (4) and DMF are added to a reaction container, and after the reaction, a compound of formula (5) is obtained, wherein the compound of formula (3): the compound of formula (4) = 1:1.5-3; wherein the equivalent of potassium phthalimide of the compound of formula (4) is in the range of 1.5-3eq, and the reaction is carried out in a dimethylformamide (DMF) solvent at 80-100°C for 10-20 hours, and the reaction of the next step is carried out only after extraction with water / dichloromethane (DCM) 3-5 times.
5. The preparation method according to claim 2, characterized in that: In the second step of the Gabriel reaction using the passivation material in step S3, at room temperature, the compound of formula (5), ethanol and tetrahydrofuran are added to the reaction container in turn, and hydrazine hydrate is added dropwise after heating. After the reaction is completed, the mixture is quenched with water, and after continuous stirring, a large amount of water / a small amount of dichloromethane is used for multiple extractions to obtain a compound of formula (6), wherein the compound of formula (5): hydrazine hydrate = 1:2-6; wherein the concentration of hydrazine hydrate used is 80% aqueous solution, and ethanol (EtOH) is used as the reaction solvent for reflux reaction for 1-2 hours. In addition, according to the solubility of different reactants, the ratio of tetrahydrofuran (THF) and ethanol added as auxiliary dissolving solvents is between 1:50 and 1:
200. After the reaction is completed, the mixture is quenched with water, and after continuous stirring for 1-5 hours, a large amount of water / a small amount of dichloromethane is used for multiple extractions. After complete water removal, no further purification is required.
6. The preparation method according to claim 2, characterized in that: In the ammoniation reaction of the passivation material in step S4, the compound of formula (6) and ethanol are added to a reaction container, and a hydroiodic acid aqueous solution is added dropwise with a separatory funnel. After stirring for two hours, the solvent is evaporated, and the equivalent should be controlled within the range of 1 to 1.5 eq. The obtained solid is recrystallized to obtain a compound of formula (8), wherein the compound of formula (6): hydroiodic acid = 1:1 to 1.5; the hydroiodic acid aqueous solution is a 57% hydroiodic acid aqueous solution, and its equivalent is controlled within the range of 1 to 1.5 eq. The obtained solid is washed with a mixed solvent of ether: dichloromethane 100:1 to 10:1, and recrystallized with ethanol or methanol.
7. The use of the dipole carbazole ammonium salt passivation material according to claim 1, characterized in that: The passivation material is used in a spin coating process with different concentrations to prepare a single-cell perovskite solar cell, a perovskite / crystalline silicon stacked solar cell or a perovskite / perovskite stacked solar cell.
8. The use according to claim 7, characterized in that: The band gap of the passivated perovskite component ranges from 1.48 to 1.80 eV.
Citation Information
Patent Citations
Solar cell and preparation method thereof
CN118201377A